Legal Analysis of The Application of Right to be Forgotten (RTBF) in Acquittal Verdicts: Implications for The Restoration of Inmates' Rights within The Indonesian Criminal Justice System - Alfin Suherman; Riswadi Riswadi (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This research examines the potential application of the Right to Be Forgotten (RTBF) in Indonesia's criminal justice system, focusing on individuals who have been acquitted or have completed their sentences. The study explores the legal, social, and ethical implications of RTBF in relation to criminal records, aiming to assess how it could support the rehabilitation and reintegration of acquitted individuals. In Indonesia, criminal records often remain publicly accessible long after a person has been legally exonerated, creating barriers to social reintegration due to the stigma associated with past accusations. The study investigates the gaps in the current legal framework, such as the lack of provisions for the removal or anonymization of criminal records for acquitted individuals, and explores how RTBF could promote justice and fairness. The research uses a literature review methodology, analyzing relevant legal texts including Law No. 11 of 2008 on Information and Electronic Transactions (ITE Law), Law No. 39 of 1999 on Human Rights, and the 1945 Indonesian Constitution. The review critically evaluates the challenges and opportunities of implementing RTBF, focusing on balancing privacy rights with public safety concerns. The findings suggest that RTBF could reduce the negative impact of criminal records on individuals who have been acquitted, facilitating their reintegration into society. However, the study also highlights the challenges in implementing RTBF due to societal and legal factors. Legal reforms recommendations allow individuals to request the removal of criminal records, aligning Indonesia's legal system with international human rights standards.